Implementation of the Zoning System Policy in Bulukumba Regency - Muhammad Iqbal; Hasnawi Haris; Risma Niswaty (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
The zoning system is a system for regulating the admission process of new students according to the area of residence. This research aims (i) To study and describe the implementation of the government's zoning system policy in Bulukumba Regency in the process of admitting new students. (ii) To identify and analyze the determinant factors that support and inhibit the implementation of the zoning system policy in Bulukumba Regency in the process of admitting new students. The informants in the study were 5 people. The results of this study indicate that (i) the implementation of the zoning system policy in Bulukumba Regency has not been effective. (Ii) Internal and external supporting factors are external supporting factors for the Minister of Education and Culture Regulation No. 1884/2285 / VI / 2020. As for the inhibiting factor, namely the lack of classroom facilities and infrastructure. There are still many parents of students who do not understand PPDB online because of the different levels of education and proportions from the parents of students, the parents are not directly involved in socializing PPDB online because of Covid 19 and less PPDB online budget.